2015
DOI: 10.7860/jcdr/2015/13444.5825
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cutaneous Horn Overlying A Verruca at an Uncommon Site: Medical Marvel vs Superstitious Dilemma

Abstract: Cutaneous horn has been a matter of discussion to mankind since time immemorial and a subject of fascination for the layman. There have been instances where certain groups saw it with angst and disgust, with a person having a large cutaneous horn on an exposed area getting a dismal look. We present a case of a 64-year-old man with a giant cutaneous horn over his left gluteal region. Cutaneous horns more commonly present in the sun-exposed areas. In our case it has presented in an uncommon site. The patient had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In many histopathology reports of cutaneous horns, it revealed hyperkeratosis, papillomatosis with koilocytes showing perinuclear halo and it has no evidence of malignancy. These findings were in par with Verruca Vulgaris or in other words knows as viral warts [ 6 ]. Based on a study conducted, it was shown actinic keratosis was the most common type followed by common warts also known as Verruca Vulgaris and followed by squamous cell carcinoma and seborrheic keratosis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many histopathology reports of cutaneous horns, it revealed hyperkeratosis, papillomatosis with koilocytes showing perinuclear halo and it has no evidence of malignancy. These findings were in par with Verruca Vulgaris or in other words knows as viral warts [ 6 ]. Based on a study conducted, it was shown actinic keratosis was the most common type followed by common warts also known as Verruca Vulgaris and followed by squamous cell carcinoma and seborrheic keratosis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though cutaneous horn is a relatively uncommon entity, different cases have been described. For example, Bo Lin et al wrote about a giant cutaneous horn on the cheek in a 83-year-old woman with an 18-year history of growth [ 1 ], Oded Nahlieli et al reported four cases occurring in the head and neck region [ 13 ], G. N. Purohit et al presented a case of a cutaneous horn following injury to pinna in a 55-year-old male farmer [ 14 ], William Leppard et al reported a case of a giant cutaneous horn of the scalp in a 52-years-old African American female [ 15 ], Michal et al described four cases of gigantic cutaneous horns of the scalp [ 16 ] and K. K. Sanjeeva et al presented a giant cutaneous horn overlying a verruca over the left gluteal region in a 64-year-old man [ 17 ]. Despite this, no one has ever focused on the causes that have allowed such an important growth of these lesions.…”
Section: Discussionmentioning
confidence: 99%